Fault and Countermeasures of Obstacle Detection in Guangzhou Metro Vehicles Door Closing - Zhuoqun CHEN (机车电传动)
Aiming at the malfunction of abnormal start of door closing obstacle detection during the main line operation of Guangzhou metro line 7 vehicle, the principle of door closing anti-pinch detection was introduced, the causes of the malfunction were deeply analyzed, and corresponding corrective measures were implemented, which effectively reduced the door failure rate.